(untitled) (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
Low budget absorption in local governments continuously distorts the quality of public services and the regional development blueprint. Grounded in agency theory, this study aims to examine and analyze the effects of budget planning, budget execution, and procurement of goods and services on the absorption of the infrastructure capital expenditure budget in Buleleng Regency. An associative quantitative approach was applied by collecting primary data through Likert-scale questionnaires distributed to respondents across four strategic Local Government Agencies (OPDs), namely PUPRPERKIM, Dishub, Bappeda, and BKAD, selected via purposive sampling. Data analysis was performed using multiple linear regression assisted by SPSS software. The empirical findings demonstrate that budget planning has no significant effect on budget absorption due to high physical complexity and field uncertainties, which degrade the function of planning documents into mere administrative formalities. Conversely, budget execution and procurement of goods and services exert a positive and significant effect, with the procurement of goods and services acting as the most dominant predictor of budget absorption. These results imply that agent accountability cannot be secured solely through ex-ante control instruments; rather, it is determined by the agent’s operational capacity to reduce agency costs during the execution phase. Practically, the Government of Buleleng Regency is urged to implement early tender strategies and simplify the bureaucracy for milestone payment disbursements to minimize administrative bottlenecks and achieve the minimum infrastructure mandatory spending target